1994
DOI: 10.1002/amo.860040409
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic non‐linearities of some stilbazolium derivatives and the calculatium derivatives and the calculation of their molecular hyperpolarisability

Abstract: The synthesis of some optically non-linear stilbazolium salts is described. Since their solid state non-linearities were small, MOPAC5 was used to compare their relative molecular non-linearities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…ear optical properties of hemicyanine compounds with halogenide counter ions were investigated by for instance Bruce et al (1994), Lupo et al (1988) and by Grummt et al (1996). Wang et al (1994aWang et al ( , 1994b) synthesized hemicyanine compounds with an anionic rare-earth tetrakis β-diketonate compounds as counter ions, instead of halogenide counter ions (fig.…”
Section: Nonlinear Optical Materialsmentioning
confidence: 99%
“…ear optical properties of hemicyanine compounds with halogenide counter ions were investigated by for instance Bruce et al (1994), Lupo et al (1988) and by Grummt et al (1996). Wang et al (1994aWang et al ( , 1994b) synthesized hemicyanine compounds with an anionic rare-earth tetrakis β-diketonate compounds as counter ions, instead of halogenide counter ions (fig.…”
Section: Nonlinear Optical Materialsmentioning
confidence: 99%
“…It is of interest that related studies involving julolidine−stilbazolium salts were found to result in moderate χ (2) values …”
Section: Introductionmentioning
confidence: 99%
“…It is of interest that related studies involving julolidine-stilbazolium salts were found to result in moderate χ (2) values. 11 The julolidyl functionality was expected to result in more efficient π-donation by allowing more efficient overlap with the aromatic ring and by virtue of the ortho-substitution, which had been shown to result in increased values of χ (2) in related derivatives (p-nitroaniline; β ) 35 × 10 -30 esu vs MNA (2-methyl-4-nitroaniline); β ) 42 × 10 -30 esu). In this case, incorporation of the julolidyl functionality had a pronounced effect resulting in χ (2) values that were less than that of the standard, urea.…”
Section: Introductionmentioning
confidence: 99%
“…Before discussing the SHG efficiency of MPMS + I - , it is interesting to compare the second-order NLO properties of the new MPMS + chromophore versus those of the well-known DAMS + -related molecule. ,,, The UV−visible spectra of MPMS + I - and DAMS + I - recorded in ethanol are compared in Figure . It can be easily observed that both chromophores exhibit a similar intense, low-lying transition located at 484 nm (ε = 46200 mol -1 cm -1 ) and 481 nm (ε = 40 800 mol -1 cm -1 ) for MPMS + I - and DAMS + I - , respectively.…”
Section: Resultsmentioning
confidence: 99%